Comprehensive molecular epidemiology of Acinetobacter baumannii from diverse sources in Nigeria - Samuel O. Ajoseh; Abdul-Azeez A. Anjorin; Wasiu O. Salami; Hanka Brangsch; Heinrich Neubauer; Gamal Wareth; Kabiru O. Akinyemi (BMC Microbiology)
Abstract Background Acinetobacter baumannii, a Gram-negative bacterium, is a public health threat due to its role in nosocomial infections and increasing antibiotic resistance. In Nigeria, data on the molecular epidemiology of A. baumannii is scarce. This study investigates the genetic diversity and the presence of antimicrobial resistance determinants and virulence-related genes in whole-genome sequencing data of 189 Nigerian A. baumannii isolates deposited in public repositories. Genotypes were determined in-silico by multilocus sequence typing (MLST) and core genome MLST (cgMLST). Further, antimicrobial resistance (AMR) and virulence-related genes were analyzed. Results Most isolates (57.67%) originated from South-west Nigeria. Isolates of human origin accounted for 33.86%, while environmental sources comprised 6.87%, and 59.27% lacked information on the source of isolation. The cgMLST analysis revealed a multitude of genomic lineages circulating in Nigeria. The MLST Oxford scheme identified 44 sequence types (STs) in 62.96% of strains, with ST1089 being the most prevalent. The MLST Pasteur could assign 95.77% of strains to 49 STs, with ST2(IC2) and ST85(IC9) being the most dominant. Antimicrobial resistance analysis detected 168 genes encoding resistance to 12 antibiotic classes, with cephalosporin, carbapenem, and aminoglycoside resistance genes being the most prevalent. Notably, bla ADC−79 (23.81%), bla OXA−23 (30.69%), and aph(3″)-Ib (30%) were frequent variants encountered. Seventeen multi-efflux system genes conferring resistance to multiple antibiotic classes were identified. Virulence gene analysis revealed 137 genes encoding six mechanisms, with genes for nutritional factors, effector delivery systems, and biofilm production being the most prevalent. Conclusion This study highlights the diversity in AMR and virulence genes of A. baumannii in Nigeria, emphasizing the need for ongoing genomic surveillance to inform infection control and develop antibiotic resistance management strategies.